Fragmentação e hidrodesoxigenação dos resíduos de canade-açúcar via processo Organosolv catalítico para a produção de bio-óleo - Wurzler, Gleicielle Tozzi (2019)
This work studied the delignification of sugarcane bagasse via catalytic Organosolv treatment using isopropanol as solvent and in situ hydrogen donor in the presence of commercial Ni-Raney catalyst and bulk Mo2C and supported in activated carbon (AC) or γ-Al2O3. These reactions were repeated to evaluate the treatment of bagasse and straw by adding H2 ex situ and in the presence of the Mo2C/AC catalyst. For reactions without H2 ex situ, the degree of delignification, the composition of the bio-oil and the solid residues depended on the type of catalyst. The reaction with bulk Mo2C exhibited the highest delignification degree (80 %). The Ni-Raney catalyst acted on hemicellulose-derived structures to form large amounts of acids, alcohols and furan derivatives. However, Mo2C type catalysts were more selective to lignin derived products, promoting the formation of benzene aromatics (~340 µg mgbiooil-1 reaction with Mo2C/AC). Enzymatic hydrolysis of post-reaction residues was also evaluated. Better yield and glucose concentration were obtained with the pretreated solid residue from carbide-based catalyst treatments. Mo2C/AC catalyst showed the highest yields and glucose concentrations (67 % and 13.7 g L-1, respectively). H2 ex situ reactions favored delignification and retention of carbohydrates in the solid phase. The detection of hydrocarbons was not considerable. However, Mo2C/AC is a promising catalyst for the recovery of different biomass fractions in a biorefinery.